Homo Sapiens, Homo Faber and Homo Dictyous. Creatively united by computing science - Mamali, Cătălin (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The present essay is a reflection inspired by the excellent book “Human Face of Computing” (editor Cristian S. Calude, published by Imperial College, Press, 2016) that is the outcome of a participatory exploration carried out by and insider (C. Calude) on the history of computing science with with its wide and deep ramification that are influencing all human activities. The book is based on interviews with outstanding researchers in computing science, mathematics, Internet, physics and technological sciences who have landmark contributions to computing science and are deeply interested in its applications, impact, uses and abuses in social life. The book explores the consequences of this field on the quality, production and democratization of knowledge.